Web and wireless geographical information systems : 12th International Symposium, W2GIS 2013, Banff, AB, Canada, April 4-5, 2013. Proceedings - Wang, Xin; Claramunt, Christophe; Liang, Steve H. L. (Lecture notes in computer science, 2013)
This book constitutes the refereed conference proceedings of the 12th International Symposium, W2GIS 2013, held in Banff, Canada, in April 2013. The 11 revised full papers and 5 short papers presented were carefully selected from 28 submissions. The program covers a wide range of topics including Spatial Semantics and Databases, Location-based Services and Applications, Trajectory Representation and Sensor Web, Spatial Analysis and Systems and Map Generation and Modeling.